Atmospheric and Hydrologic interactions at regional and climatic scales. The West African Monsoon case. - (:unkn) unknown (My University, 2005)
The use of the regional climate model MAR (dx=40km) over the West Africa showed that the simulated pluviometric regime and the simulated dynamics are mainly influenced by the Gulf of Guinea SST during 1984. This sensitivity is strongly marked up to 12°N. Beyond this limit, the precipitation regime seems mainly influenced by the interactions with the continental surfaces and the synoptic features. The Sahelian region thus appears as relevant in order to study the coupling between the atmosphere and the continental surfaces. A new coupling architecture has been then built with the aim to use legacy models and to ensure modularity, portability, extensibility and interoperability. It has been first tested in a one-way configuration by a forcing of the hydrologic model ABC (dx~1.8 km) applied over the Sirba watershed (39000 km2) by rainfall fields. The use of a temporal disaggregation method considering several maximums in a single convective event has demonstrated the larger influence of the time sampling comparing to the spatial location of the rainfall over the basin. Finally, a fully coupled experiment between the MAR model, a SVAT (Surface Vegetation Atmosphere Transfer) model and the ABC model has been performed over the Sahelian Sirba catchment. The effects of the SVAT grid refinement over the Sirba basin are responsible for changes in soil surface temperature, sensible and latent heat fluxes and soil water balance. However, these modifications can be modulated by the hydrologic model which is able to modify the infiltration and consequently the soil surface water balance and therefore the energy budget and the albedo as well.
Keywords: African Research